Business cycles in the Czech Republic an empirical investigation - Bocák, Petr; Pošta, Vít, 1980-; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
The aim of this thesis is to estimate monthly probability that the Czech economy is in a recession. For this purpose, I construct indexes of coincident and leading variables from multiple time series by Maximum Likelihood. Changes in coincident index are preceded by changes in the leading index by almost one year for peaks and about one month for troughs on average. To assess the probability of recession, I estimate multiple mixture models for growth rates of coincident index focusing on Markov-Switching specification for the latent business cycle process. I found that the two-state Markov-Switching AR (1) is superior to other models based on information criteria. Lagged values of leading index further improve the model fit but the model provides less clear signals of recessions compared to models based solely on coincident index.
Vedoucí práce: Vít Pošta
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses